A Retrospective Analysis of Randomized Controlled Trials on Traumatic Brain Injury: Evaluation of CONSORT Item Adherence - Meltem Elcivan; Ana Kowark; Mark Coburn; Hussam Aldin Hamou; Benedikt Kremer; Hans Clusmann; Anke Höllig (Brain Sciences, 2021)
Traumatic brain injury (TBI) contributes to death and disability, resulting in an enormous individual and socio-economic challenges. Despite huge efforts, there are still controversies on treatment strategies and early outcome estimation. We evaluate current randomized controlled trials (RCTs) on TBI according to their fulfillment of the CONSORT (Consolidated Statement of Reporting Trials) statement’s criteria as a marker of transparency and the quality of study planning and realization. A PubMed search for RCTs on TBI (January 2014–December 2019) was carried out. After screening of the abstracts (n = 1.926), the suitable full text manuscripts (n = 72) were assessed for the fulfillment of the CONSORT criteria. The mean ratio of consort statement fulfillment was 59% (±13%), 31% of the included studies (n = 22) complied with less than 50% of the CONSORT criteria. Citation frequency was moderately related to ratio of CONSORT item fulfillment (r = 0.4877; p < 0.0001) and citation frequency per year (r = 0.5249; p < 0.0001). The ratio of CONSORT criteria fulfillment was associated with the impact factor of the publishing journal (r = 0.6428; p < 0.0001). Essential data for study interpretation, such as sample size determination (item 7a), participant flow (item 13a) as well as losses and exclusions (item 13b), were only reported in 53%, 60% and 63%, respectively. Reporting and methodological aspects in RCTs on TBI still may be improved. Thus, the interpretation of study results may be hampered due to methodological weaknesses.